2014
DOI: 10.4097/kjae.2014.66.5.358
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different mechanical ventilator settings of peak inspiratory pressure on stroke volume variation in pediatric cardiac surgery patients

Abstract: BackgroundThe usefulness of dynamic parameters derived by heart-lung interaction for fluid responsiveness in pediatric patients has been revealed. However, the effects of peak inspiratory pressure (PIP) that could affect the absolute values and the accuracy in pediatric patients have not been well established.MethodsParticipants were 30 pediatric patients who underwent ventricular septal defect repair. After completion of surgical procedure and sternum closure, mean arterial blood pressure, heart rate, central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although an absence of spontaneous breathing was confirmed clinically by observing the capnograph waveform, variations in PIP, and the animal's chest movements, it is possible that small respiratory efforts affected values of PPV and PVI because a neuromuscular blocking agent was not used. Second, the measurement of PPV and PVI can be directly affected by a change in TV, PIP, and a pleural pressure . In this study, the relatively high VT of 15 mL/kg was set in order to avoid a low VT that may produce unreliable PPV, but the current study's setting resulted in clinically acceptable PIP and P ETCO2 (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…Although an absence of spontaneous breathing was confirmed clinically by observing the capnograph waveform, variations in PIP, and the animal's chest movements, it is possible that small respiratory efforts affected values of PPV and PVI because a neuromuscular blocking agent was not used. Second, the measurement of PPV and PVI can be directly affected by a change in TV, PIP, and a pleural pressure . In this study, the relatively high VT of 15 mL/kg was set in order to avoid a low VT that may produce unreliable PPV, but the current study's setting resulted in clinically acceptable PIP and P ETCO2 (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it was reported recently that the predictive value of dynamic parameters may be influenced by other settings of mechanical ventilation besides tidal volume in children. Kang et al [ 33 ] studied the influence of different peak inspiratory pressure (PIP) on SVV in pediatric cardiac surgery patients, and the result showed that SVV was affected by different levels of PIP in same patient and under same volume status. In consideration of the differences between the physiology in children and adult patients, further studies are needed to explore the optimal tidal volume and other parameters of mechanical ventilation for children.…”
Section: Discussionmentioning
confidence: 99%
“…However, past studies have reported that the following factors influenced SVV: tidal volume, compliance of thoracic wall, and positive‐end expiratory pressure (PEEP) . Moreover, various respiratory settings are currently used in the care of critically ill patients; thus, we should understand the mechanism on how SVV changes under various respiratory settings and preloads …”
Section: Introductionmentioning
confidence: 99%